IMPLEMENTING SURFACE STRUCTURE TAXONOMY IN ANALYZING UNDERGRADUATE STUDENTS’ BUSINESS E-MAIL ERRORS - Desnaranti, Laila; Putra, Febby Pratama (Research and Development Journal of Education, 2024)
Because of technological advancements, email (electronic mail) has become a common tool for business communication and transactions. That is why, one of the topic that undergraduate students learn in business English course is how to write formal email. Error analysis plays a vital function in assisting lecturers in identifying the kind of errors that undergraduate students make most frequently in their writing as well as the reasons behind those errors. Based on the issues that have been discussed before, the researchers would like to investigate what are the errors in the formal email that the undergraduate students write. The researchers also want to determine which kind of errors that the undergraduate students most and least produce. This research use surface structure taxonomy to explore errors that undergraduate students made in their formal business emails. Following extensive deliberation and meticulous examination of data from 68 formal emails written by undergraduate students, the researcher found that there are 27 (39,7%) omission erorrs,  19 (27,9%) addition errors, 12 (17,6%) misformation errors, and 10 (14,7%) misordering errors. From the analysis result, the most errors which is done by the undergraduate students in their formal email is omission error and the least is misordering errors.